PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DI PT CAHAYA SAMUDRA SHIPYARD - Kang, Leslie; Saputra, Asron (LPPM Universitas Putera Batam, 2022)
Quality human resources and the creation of job satisfaction for employees and produce something that meets the expectations of a company, because the company must pay attention to the needs of employees such as occupational safety and health. It often happens that companies ignore work safety. The findings of this study have a purpose to understand the effect of occupational safety and health on job satisfaction at PT Cahaya Samudra Shipyard. The technique of taking a sample using a saturated sample. For the purpose of data collection, the researcher distributed a questionnaire, which included a list of questions to be answered by the participants. The method used in the findings contained in this study is a quantitative-based research by conducting multiple linear analysis. The results obtained from a finding contained in a study prove that occupational safety and health can have a significant effect on job satisfaction of employees of PT Cahaya Samudra Shipyard.